2012
DOI: 10.1155/2012/736384
|View full text |Cite
|
Sign up to set email alerts
|

Spondyloarthropathies in Autoimmune Diseases and Vice Versa

Abstract: Polyautoimmunity is one of the major clinical characteristics of autoimmune diseases (ADs). The aim of this study was to investigate the prevalence of ADs in spondyloarthropathies (SpAs) and vice versa. This was a two-phase cross-sectional study. First, we examined the presence of ADs in a cohort of patients with SpAs (N = 148). Second, we searched for the presence of SpAs in a well-defined group of patients with ADs (N = 1077) including rheumatoid arthritis (RA), systemic lupus erythematosus (SLE), and Sjögre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 31 publications
0
10
0
2
Order By: Relevance
“…Note: Although AS is considered an auto-inflammatory more than autoimmune disease [76] we show the results obtained.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Note: Although AS is considered an auto-inflammatory more than autoimmune disease [76] we show the results obtained.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 3 and Table 1 summarize the search results. Although ankylosing spondylitis (AS) is considered an auto-inflammatory more than autoimmune disease [76], it was included in the results since it was found to aggregate in families. Most of the studies found lacked controls and had a small sample size, which is reflected in low grading according to the 2011 levels of evidence from the Oxford Centre for Evidence-based Medicine [28].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When the topic is poly-autoimmunity or multiple autoimmune syndrome, i.e., co-existence of more than two autoimmune diseases, than genetic analysis of the affected families helps to assess the risk (Ribbhammar et al, 2003;Criswell et al, 2005;Perez-Fernandez et al, 2012). On the other hand, models that reproduce autoimmune conditions (or phases of these conditions) are needed for experimental research.…”
Section: Resultsmentioning
confidence: 99%
“…The first comes from clinical observations indicating the possible shift from one disease to another or to the fact that more than one AD may coexist in a single patient (i.e., polyA, MAS) [24,[36][37][38][39] in the same family (i.e., familial autoimmunity) [40]. The second level of evidence refers to known shared pathophysiological mechanisms between ADs [41]; and the third level of evidence corresponds to the evidence implying common genetic factors [38].…”
Section: Discussionmentioning
confidence: 99%